Intranasal immunization of mice with herpes simplex virus type 2 recombinant gD2: the effect of adjuvants on mucosal and serum antibody responses. - Ugozzoli, M (1998)
Mucosal immunization offers the potential for inducing IgA antibody responses in the vagina, the site of infection for many viruses, including herpes simplex type 2 (HSV-2). To investigate this possibility, mice were immunized intranasally with 10 micrograms glycoprotein D2 (gD2) from HSV combined with a series of adjuvants of proven efficacy; the oil in water emulsion MF59, poly(D,L-lactide-co-glycolide) microparticles (PLG) (encapsulated or co-administered), immune-stimulating complexes (iscoms) (incorporated or co-administered with iscomatrix) and the genetically detoxified enterotoxin from Escherichia coli, LT-K63. Encapsulation of gD2 into PLG microparticles, incorporation of gD2 into iscoms and co-administration of gD2 with LT-K63 induced mucosal IgA antibody responses (nasal wash, saliva and vaginal wash) which were greater than those induced by intramuscular administration of gD2 with MF59. Intranasal immunization with these formulations also induced substantial levels of serum IgG and neutralizing antibodies. These studies demonstrated that intranasal immunization with potent adjuvants is an effective means to induce mucosal antibody responses, even in the lower genital tract.